Internalisasi Nilai-Nilai Islami Melalui Program Wajib Diniyah - Muhamad Ansori (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2022)
Abstract: Diniyah is an alternative supporting institution in carrying out the activities of internalizing Islamic values ​​to students, aspects of Islamic values ​​consist of three things, namely the value of aqidah, worship and morals, these values ​​are very important for Islamic education in this era. The focus of the research in this study is 1) how is the implementation of the compulsory Diniyah program at SMA Plus Darul Hikmah Jember?, 2) what are the methods used by institutions and educators in internalizing the Islamic values ​​of students through the compulsory Diniyah program at SMA Plus Darul Hikmah?, 3 ) how is the impact of the compulsory Diniyah program on the Islamic values ​​of students at SMA Plus Darul Hikmah Jember?, 4) what are the supporting and inhibiting factors for the role of the compulsory Diniyah program in internalizing the Islamic values ​​of students at SMA Plus Darul Hikmah Jember?. The research method used is a qualitative research method, using purposive sampling technique with data collection through observation, interviews and documentation. The data analysis used is Miles and Hubermen, namely: data reduction, data display, and leverage. The validity of the data using source triangulation. The results of this study indicate that the implementation of the compulsory Diniyah program is structured with a structured and regular system foundation, with the habit of praying dhuha at 06.30, the implementation of learning is one hour, in the morning from 07.00 to 08.00 with lecture, practice, answer, memorization, and story methods. -story. The positive impact resulting from the Diniyah program is that students are more able to maintain their aqidah/faith in the face of deviant teachings, students develop better attitudes/morals, the application of aspects of worship is more widespread in terms of application to aspects of worship/fiqh. While the negative impact: memorization becomes a burden for students. Keywords: Internalization of Islamic Values, Compulsory Diniyah Program